2018
DOI: 10.1038/s41467-018-04555-4
|View full text |Cite
|
Sign up to set email alerts
|

A multiethnic genome-wide association study of primary open-angle glaucoma identifies novel risk loci

Abstract: Primary open-angle glaucoma (POAG) is a leading cause of irreversible vision loss, yet much of the genetic risk remains unaccounted for, especially in African-Americans who have a higher risk for developing POAG. We conduct a multiethnic genome-wide association study (GWAS) of POAG in the GERA cohort, with replication in the UK Biobank (UKB), and vice versa, GWAS in UKB with replication in GERA. We identify 24 loci (P < 5.0 × 10−8), including 14 novel, of which 9 replicate (near FMNL2, PDE7B, TMTC2, IKZF2, CAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
152
2
11

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 142 publications
(167 citation statements)
references
References 71 publications
(112 reference statements)
2
152
2
11
Order By: Relevance
“…Reports have shown that incidence rate of glaucoma is higher in siblings compared with unrelated controls, indicating an important role of host genetics in predisposition to glaucoma. Recent genome wide association studies reveled role of ATP‐binding cassette transporter A1, actin filament‐associated protein 1, GDP‐mannose 4,6 dehydratase, phosphomannomutase 2, transforming growth factor beta receptor III, fibronectin type III domain containing 3B, rho guanine nucleotide exchange factor 12, growth arrest‐specific protein 7, forkhead box C1, ataxin‐2, thioredoxin reductase 2 with POAG, and PACG showed to be linked to ependymin related 1, choline acetyltransferase, gli‐similar protein 3, fermitin family member 2, and dolichyl‐phosphate mannosyltransferase subunit 2 . Furthermore, various candidate gene association studies presented association of single nucleotide polymorphisms with predisposition to development of POAG or PACG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have shown that incidence rate of glaucoma is higher in siblings compared with unrelated controls, indicating an important role of host genetics in predisposition to glaucoma. Recent genome wide association studies reveled role of ATP‐binding cassette transporter A1, actin filament‐associated protein 1, GDP‐mannose 4,6 dehydratase, phosphomannomutase 2, transforming growth factor beta receptor III, fibronectin type III domain containing 3B, rho guanine nucleotide exchange factor 12, growth arrest‐specific protein 7, forkhead box C1, ataxin‐2, thioredoxin reductase 2 with POAG, and PACG showed to be linked to ependymin related 1, choline acetyltransferase, gli‐similar protein 3, fermitin family member 2, and dolichyl‐phosphate mannosyltransferase subunit 2 . Furthermore, various candidate gene association studies presented association of single nucleotide polymorphisms with predisposition to development of POAG or PACG.…”
Section: Introductionmentioning
confidence: 99%
“…Recent genome wide association studies reveled role of ATP-binding cassette transporter A1, actin filament-associated protein 1, GDP-mannose 4,6 dehydratase, phosphomannomutase 2, transforming growth factor beta receptor III, fibronectin type III domain containing 3B, rho guanine nucleotide exchange factor 12, growth arrest-specific protein 7, forkhead box C1, ataxin-2, thioredoxin reductase 2 with POAG, and PACG showed to be linked to ependymin related 1, choline acetyltransferase, gli-similar protein 3, fermitin family member 2, and dolichyl-phosphate mannosyltransferase subunit 2. [6][7][8][9][10] Furthermore, various candidate gene association studies presented association of single nucleotide polymorphisms with predisposition to development of POAG or PACG. Role of matrix metalloproteinase-9 (MMP-9) variants have been well investigated in different populations as MMP-9 gene is responsible for remodeling of extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…POAG is highly heritable 4,5 , and previous genome-wide association studies (GWAS) have identified important loci associated with POAG risk and IOP [6][7][8][9][10][11][12][13][14] . Despite this success, the POAG genetic landscape remains incomplete and identification of novel risk loci is required to further define contributing disease mechanisms that could be targets of novel preventative therapies.…”
mentioning
confidence: 99%
“…A multi-ethnic genome-wide association study (GWAS) of the Genetic Epidemiology Research in Adult Health and Aging (GERA) cohort, which included individuals of African, Asian, Hispanic, and European descent, identified three novel and replicated variants near the PDE7B, TMCTC2, and FMNL2 genes. 39 A GWAS of South African and African American populations identified a novel candidate locus on the EXOC4 gene, but it did not associate in a West African replication cohort. 37 The African Descent and Glaucoma Evaluation Study (ADAGES) identified a novel association with advanced POAG and the EN04 locus.…”
Section: Introductionmentioning
confidence: 98%